DISFUNGSI INSTITUSI KONSERVASI DAN DAMPAKNYA PADA KEGAGALAN ADOPSI TEKNOLOGI KONSERVASI TANAH DAN AIR, STUDI KASUS DI KABUPATEN WONOGIRI DAN TEMANGGUNG, JAWA TENGAH - Nana Haryanti (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2014)
Low rate adoption of soil and water conservation technologies, such as agroforestry systems and terrace farming, is still prevalent in a number of areas proned to water erosion. One of prominence alleged factors is conservation institution, which is mostly weak in inducing community, especially farmers or landholders, to apply soil and water conservation technologies to their own farmland. By using two case studies of soil and water conservation projects inWonogiri and Temanggung regencies, this paper is aimed to explore and analyze the role of conservation institutions in the diffusion process of soil and water conservation technologies among farmers or landholders. Data were collected using in-depth interviews and focus group discussions. Institution in this research referred to institutional framework developed by Department of Foreign and International Development (DFID). They included formal conservation institutions, namely forest farmer groups, government institution, and extension agents. Results showed that the absence of conservation institutions discouraged farmers' motivation to adopt conservation technologies. Institutional dysfunction resulted in breaking of social learning processes thus decreasing community awareness and decompressing conservation norms.As an implication of this study, government policies on soil conservation and land rehabilitation should be adjusted to be more farmers or landholders oriented and should include incentives and disincentives for soil conservation and land rehabilitation activities.